Green Synthesis, Characterization, and Photocatalytic Activity of Zinc Oxide Nanoparticles on Photodegradation of Naphthol Blue Black Dye - Jesisca Silver; Surya Lubis; Muliadi Ramli (Jurnal Kimia Sains dan Aplikasi, 2023)
Zinc oxide (ZnO) nanoparticles have been successfully synthesized using water extract of red dragon fruit (Hylocereus polyrhizus) stem with zinc acetate dihydrate as a precursor of ZnO. Chemical compounds contained in the red dragon fruit stem extract, such as phenolics, terpenoids, and steroids, acted as reducing agents, stabilizers, and capping agents. The phase structure, crystallite size, functional groups, shape, and morphology of ZnO nanoparticles were determined by X-ray diffraction (XRD), Fourier Transform infrared (FT-IR) Spectroscopy, and Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX). The XRD pattern confirmed the crystallinity of synthesized zinc oxide was in the zincite (ZnO) phase with an average crystallite size of 79.09 nm. Spectroscopy FTIR analysis showed that the synthesized ZnO nanoparticles had characteristics similar to the ZnO standard/commercial. SEM-EDX analysis revealed that the synthesized ZnO nanoparticles were spherical, evenly distributed, and homogeneous particle size. The photocatalytic activity of synthesized ZnO nanoparticles was evaluated on the photodegradation of naphthol blue black (NBB) dye. The results showed that the synthesized ZnO nanoparticles have high photocatalytic activity that can degrade NBB dye up to 98.82%. This high photocatalytic activity was obtained at operating parameter conditions with the initial pH of NBB at 2, the dosage of ZnO nanoparticles at 250 mg, and the initial dye concentration at 10 ppm.